Silica-graphene oxide hybrid composite particles and their electroresponsive characteristics - Zhang, Wen Ling (Langmuir : the ACS journal of surfaces and colloids, 2012)
Silica-graphene oxide (Si-GO) hybrid composite particles were prepared by the hydrolysis of tetraethyl orthosilicate (TEOS) in the presence of hydrophilic GO obtained from a modified Hummers method. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images provided visible evidence of the silica nanoparticles grafted on the surface of GO, resulting in Si-GO hybrid composite particles. Energy dispersive X-ray spectroscopy (EDX) and X-ray diffraction (XRD) spectra indicated the coexistence of silica and GO in the composite particles. The Si-GO hybrid composite particles showed better thermal stability than that of GO according to thermogravimetric analysis (TGA). The electrorheological (ER) characteristics of the Si-GO hybrid composite based ER fluid were examined further by optical microscopy and a rotational rheometer in controlled shear rate mode under various electric field strengths. Shear stress curves were fitted using both conventional Bingham model and a constitutive Cho-Choi-Jhon model. The polarizability and relaxation time of the ER fluid from dielectric spectra measured using an LCR meter showed a good correlation with its ER characteristics